Сказки: Пер. с нем. / В. Гауф - Гауф Вильгельм (Классики и современники. Зарубеж. лит., 1988)
Экземпляры: ф.14 (20190724) / Инвентарный номер: 57437 / Цена: 10.00 / Авт.знак: Г24 / ГРНТИ: 17.82 / ББК: 84(4Гем)